2D-Speckle tracking echocardiography contributes to early identification of impaired left ventricular myocardial function in children with chronic kidney disease. (28th August 2018) - Demetgul, Hasan; Giray, Dilek; Delibas, Ali; Hallioglu, Olgu
Abstract: Introduction: The aim of this study is to determine early changes in cardiac function of children with chronic kidney disease by using 2D-speckle tracking echocardiography. Method: The study included 38 children – 16 girls and 22 boys – diagnosed as having chronic kidney disease in the nephrology department with a glomerular filtration rate of <90 ml/minute/1.73 m 2 for at least 3 months. A total of 37 – 15 girls and 22 boys – age- and sex-matched healthy children were included as the control group. 2D-Speckle tracking echocardiography was performed in all subjects. Results: The mean age was 13.45±2.8 years in patients and 12.89±3.07 years in controls. Systolic and diastolic blood pressures and left ventricular mass index were significantly higher in patients (p<0.05). The values of mitral e, mitral a, mitral e/a ratio, and mitral deceleration time were not different between the groups. Tricuspid annular plane systolic excursion values were lower in patients (p<0.01). Global strain values in apical long-axis 3-chamber and 2-chamber views were significantly lower in patients (p<0.05). Longitudinal, radial, and circumferential peak systolic strain values were lower in patients, but the difference was statistically significant in all segments of longitudinal view and basal segment of circumferential view (p<0.05). Radial and circumferential systolic strain rates were significantly lower in patients in all three segments (p<0.05). Moreover, early diastolic strain rate was significantly lower in longitudinal and radial apical segments and in all segments of circumferential measurements in patients. Besides, strain rate e/a ratio was significantly lower in all longitudinal segments of patients (p=0.01). Conclusion: The study concluded that 2D-speckle tracking echocardiography method can determine cardiac involvement earlier than conventional echocardiography in children with chronic kidney disease having preserved ejection fraction.